DEVELOPMENT OF MATHEMATICS PICTURE STORY BOOK ON FRACTION MATERIAL FOR GRADE IV ELEMENTARY SCHOOL STUDENTS - Mananggel, Marlin Blandy; Ramadhani, Widya Putri; Makaruku, Yulian Hani (Jurnal Pendidikan Matematika (JUPITEK), 2024)
Mathematics picture story books are learning media that can help students learn mathematics content both independently or through active interaction in the classroom. This study aims to develop learning media for mathematics picture story books on Fraction material and determine its feasibility for grade IV elementary school students. This research is an R&D research with ADDIE model which consists of stages 1) analyze, 2) design, 3) development, 4) implementation, and 5) evaluate. The subjects in this study were 40 fourth grade students at SD Negeri 318 Maluku Tengah, SD Negeri 254 Maluku Tengah and SD Kristen Tiouw. Before being tested, this book was first validated by material experts and media experts. This research produces a product in the form of illustrated storybooks as a medium for learning mathematics on Fraction material. Based on the assessment of material experts get a validity percentage of 89% category "Very Valid" while the assessment of media expert validators get a validity percentage of 92% category "Very Valid" to be used in grade IV elementary students. Based on the response of students, it gives a practicality value of 93.86% in the "Very Practical" category for picture storybook media products. Based on the test results, the average student score is 71.77 and it is above the Minimum Completeness Criteria, meaning that the picture story book is considered "very effective" to be used publicly. Because it meets all the criteria, the picture story book is said to be "very feasible" to use. This picture story book can help students improve learning outcomes and foster student curiosity so as to increase understanding and reasoning about mathematics, especially fraction material